The Agricultural Irrigation District Information System based on Multi-Agent - Tinghong Zhao; Zibin Man; Huimin Hou (Institute of Advanced Engineering and Science, 2014)
Irrigation district informative construction is an effective way to improve the management and to rational allocate and effectively utility irrigation water resources. This paper is directed against the characteristics such as large-scale monitoring data amount, complex data types, high real-time requirement, strong spatial correlation, etc. combine Multi-Agent theory with irrigation district information system together, and use GSM communication network as the communication network of system, established an agricultural irrigation district information system based on Multi-Agent and GSM, which can full utility intelligent of Agent and the good communication coordination of Multi-Agent system, so to provide comprehensive technical support for irrigation management and decision making. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.3583